Phagocyte Responses to Cell Death in Flies. - Davidson, A.J.; Wood, W. (Cold Spring Harbor perspectives in biology, 2020)
Multicellular organisms are not created through cell proliferation alone. It is through cell death that an indefinite cellular mass is pared back to reveal its true form. Cells are also lost throughout life as part of homeostasis and through injury. This detritus represents a significant burden to the living organism and must be cleared, most notably through the use of specialized phagocytic cells. Our understanding of these phagocytes and how they engulf cell corpses has been greatly aided by studying the fruit fly, Drosophila melanogaster Here we review the contribution of Drosophila research to our understanding of how phagocytes respond to cell death. We focus on the best studied phagocytes in the fly: the glia of the central nervous system, the ovarian follicle cells, and the macrophage-like hemocytes. Each is explored in the context of the tissue they maintain as well as how they function during development and in response to injury.